CAPITAL CITIES: FROM HISTORIC TO MODERN - Baykabilov, Kh.M. (SCIENCE and SOCIETY, 2025)
The article examines the historical development and modern interpretation of world capitals. In addition, describes the analysis of classification groupings based on the geographical features of capitals.
Keywords: capital; city; historicity; modernity; classification; classification units